A gestão de pessoas em centros de serviços compartilhados no Brasil: um estudo sobre a percepção dos gestores e empregados operacionais - Cunha, Júlio Araujo Carneiro da (2011)
Studies from Management area are concentrated in understanding organizational core activities, while few efforts were given to comprehend staff activities and the way they can add value. So, organizational structures such as shared services centers (SSCs) are presented not only as relevant objects to academic studies, but also as a demand, since there is an expansion in this staff activities service model in bigger organizational groups. Before this, there is a specific labor environment that is not fully understood from the Human Resources (HR) perspective, being important to understand the perceptions of SSC employees (managers and operational workers) on Human Management practices and organizational characteristics. Based on this, the objective of this study is to verify how the characteristics and practices related to Human Management at SSCs are configured through managers and operational workers perceptions. Considering a literature review of SSCs characteristics harnessed with the human resources management in these structures, along with HR Strategic Management, a theoretical framework was established and analysis categories were defined. Through case study method, four SSCs installed at Brazil were studied and 44 personal interviews were done (seven with managers and 37 with operational analysts). Results guided to the identification of the following categories: (a) HR area; (b) Professional development; (c) labor characteristics; (d) people management politics. It was concluded that the non-existence of a Human Management department oriented to intern SSC employees, slows the human management capabilities; there must be awareness with stringent models because mature SSCs varies internally; SSCs are excellence centers for operational knowledge; line managers should be better trained to enhance their relations with employees.